Relação dos principais padrões de oscilação do vento na baixa atmosfera e a temperatura mínima mensal no Rio Grande do Sul - Pedra, George Ulguim (2011)
Rio Grande do Sul (RS) has a large annual temperature range is characterized by hot summers and cold winters, being strongly influenced by weather systems in middle and high latitudes. Many studies suggest climate change on Earth, particularly to the anomalous increase in temperature in recent decades. The large thermal variations interfere directly in agricultural production, trade and tourism, affecting the region's economy. The main objective of this research was to identify the main patterns of wind speed at 850hPa layer. This layer is slightly above the surface outside of each boundary, and thus with little influence of urban effects. Knowing the correlation of patterns of wind speed with variations of monthly minimum temperatures throughout the year in RS, identify and compare the adjustment functions of temporal trends linear and nonlinear, and list the possible influence of large swings over the Pacific Ocean these variations regional, especially during extreme. To study the atmospheric oscillations were used in data grid point wind speed at 850hPa over South America, which were applied the technique of spectral decomposition defined principal components. We used monthly minimum temperature data from 24 stations well distributed spatially in RS. The results showed that the patterns of oscillations Main circulation in the lower atmosphere over South America are strongly associated with variations of wind speed in regions of the Polar Jet, Subtropical Jet and the trade winds in the Equatorial Pacific. Core Standards of the wind speed did not correlate significantly with the minimum temperatures in March, June, July and September. During other months the correlation coefficients were significant, especially the months of January, April, May and October. The northern state of RS presented highlight this relationship, with the months of April and May the most significant. The trend of monthly minimum temperatures for the meteorological station of Irai shown for all months of the year, the biggest adjustment function non-linear time in comparison with the linear. The index of the Pacific Decadal Oscillation function showed nonlinear fitting, revealing very similar function to the main circulation patterns of the wind at 850hPa and adjustments of nonlinear functions of minimum temperatures in Iraí (RS). Faced with the obvious relations between the oscillations of the wind circulation at 850hPa with the changes in the surface equatorial Pacific / North, we can expect that the trends in minimum temperatures in RS for these next two decades suffer on average more negative than oscillations positive, especially during summer and autumn, although it indicates increased temperature in early spring.